THE INFLUENCE OF REGIONAL TAX REVENUE ON REGIONAL ORIGINAL INCOME WITH GOOD CORPORATE GIVERNANCE AS A MODERATING VARIABLE - Doke, Herlina Theodensia D.; Usnmany, Paul; Aninam, Johny; Kalalo, Rieneke Ryke; Eljawati, Eljawati (ITB AAS Indonesia Surakarta, 2024)
ABSTRACT This research is quantitative research with an exploratory approach, namely an approach that uses the five studies above as the main springs for building a new water source center which researchers will design with new variations or what is usually called an element of novelty in each study. The data used in this research is secondary data that researchers obtained from the Central Bureau of Statistics to see the tax revenue of each province in the last 10 years which is published every year on the official website of the Central Bureau of Statistics. These data were analyzed using the smart PLS 4.0 analysis tool. The result in this article show Regional Tax Revenue can have a positive relationship and a significant influence on Regional Original Income. This can be caused because the P-Values value is positive and is below the 0.05 significance level, namely 0.019. Based on these results, it can be concluded that the more tax revenue a region receives can increase its Original Regional Income. What is different from the five studies above, in the next row of the third table of this study shows that the Good Corporate Governance variable can strengthen the influence of the Regional Tax Revenue variable on Regional Original Income. This is because the P-Values value is positive and is below the 0.05 significance level, namely 0.000. Thus the first and second hypotheses in this research can be accepted. Keywords: Regional Tax Revenue, Regional Original Income, Good Corporate Givernance.